2019
DOI: 10.1038/s41598-019-53603-6
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 inhibition as a novel therapeutic target for alcoholic liver disease

Abstract: Alcoholic liver disease (ALD) causes significant morbidity and mortality, and pharmacological treatment options are limited. In this study, we evaluated the PCSK9 inhibitor alirocumab, a monoclonal antibody that robustly reduces low-density lipoprotein cholesterol (LDL-C), for the treatment of ALD using a rat model of chronic alcohol exposure. Alirocumab (50 mg/kg) or vehicle was administered weekly for 6 weeks to rats receiving a 12% alcohol liquid diet or an isocaloric control diet. At the end of the alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 75 publications
3
52
1
Order By: Relevance
“…The PCSK9 inhibitor, which upregulates LDLR, is currently being used as the second line treatment of hypercholesterolemia (52). Interestingly, treatment with PCSK9 inhibitor has been shown to ameliorate alcoholic fatty liver disease (53) and PCSK9 may be involved in NAFLD development in experimental models and patients (54). Although these beneficial effects may be partially attributed to the reduction of cholesterol, the present findings suggest that PCSK9 inhibition can ameliorate NAFLD via a mechanism independent of LDL cholesterol reduction, by enhancing the LDLR-dependent miR-223enriched EV uptake by hepatocytes which then inhibits liver inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The PCSK9 inhibitor, which upregulates LDLR, is currently being used as the second line treatment of hypercholesterolemia (52). Interestingly, treatment with PCSK9 inhibitor has been shown to ameliorate alcoholic fatty liver disease (53) and PCSK9 may be involved in NAFLD development in experimental models and patients (54). Although these beneficial effects may be partially attributed to the reduction of cholesterol, the present findings suggest that PCSK9 inhibition can ameliorate NAFLD via a mechanism independent of LDL cholesterol reduction, by enhancing the LDLR-dependent miR-223enriched EV uptake by hepatocytes which then inhibits liver inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are no standardized procedures for the alcohol liquid diet across laboratories, and the concentration of alcohol in the diet varies considerably (e.g., 5 to 35%). However, this unique approach results in BALs that are sufficient to induce liver damage, intoxication, tolerance, dependence, and withdrawal (Gilpin et al, ; Lee et al, in press). Equally effective in producing alcohol dependence is the chronic, intermittent alcohol vapor exposure model, where animals are typically exposed to alcohol vapor for 14 h/d (intoxication), followed by 10 hours with vapor off (withdrawal).…”
Section: Preclinical Models To Investigate the Intersection Of Aud Anmentioning
confidence: 99%
“…In animal models, LPS could regulate the expression of PCSK9 mRNA [ 43 ]. Interestingly, in a recent study, significant elevation was found in PCSK9 and inflammatory factors in the rat model of alcohol liver disease, whereas there was a significant inhibition of inflammatory reaction after administration of anti-PCSK9 agents [ 44 ]. Thereby, it was proposed that PCSK9 may directly trigger the inflammatory reactions in the pathogenesis of alcohol liver disease.…”
Section: Role Of Pcsk9 In the Pathogenesis Of Sepsismentioning
confidence: 99%